Răspuns :
Răspuns:
Explicație pas cu pas:
[tex]\sqrt({2-\sqrt{5} } )^{2} =\sqrt{5}-2\\ \sqrt({2+\sqrt{5} })^{2} =2+\sqrt{5} \\x(\sqrt{5} -2-2-\sqrt{5})=-2-\sqrt{5} -\sqrt{5} +2\\ -4x=-2\sqrt{5} \\x=\frac{\sqrt{5} }{2}[/tex]
Răspuns:
[tex]x = \frac{ \sqrt{5} }{2} \\ [/tex]
Explicație pas cu pas:
[tex]x \sqrt{(2 - \sqrt{5}) {}^{2} } + \sqrt{( 2 - \sqrt{5} ) {}^{2} } = x \sqrt{(2 + \sqrt{5}) {}^{2} } - \sqrt{(2 + \sqrt{5} ) {}^{2} } \\ [/tex]
[tex]x( \sqrt{5} - 2) + \sqrt{5} - 2 = x(2 + \sqrt{5} ) - (2 + \sqrt{5} ) \\ [/tex]
[tex] \sqrt{5} x - 2 x + \sqrt{5} - 2 = 2x + \sqrt{5} x - (2 + \sqrt{5} ) \\ [/tex]
[tex] - 2x + \sqrt{5} - 2 = 2x - 2 - \sqrt{5} [/tex]
[tex] - 2x + \sqrt{5} = 2x + \sqrt{5} [/tex]
[tex] - 2x - 2x = - \sqrt{5} - \sqrt{5} [/tex]
[tex] - 4x = - 2 \sqrt{5} [/tex]
[tex]x = \frac{2 \sqrt{5} }{4} = \frac{ \sqrt{5} }{2} \\ [/tex]